Electrical Impedance Characteristics of Slug Flow in Small Channels and its Application to Void fraction Estimation. (November 2022) - Huang, Junchao; Jiang, Yandan; Ji, Haifeng; Wang, Baoliang; Huang, Zhiyao
Highlights: Investigate slug flow electrical impedance characteristics in small channels. Reveal influence of the slug velocity on the relationship: impedance-void fraction. Explain how the slug velocity influence the relationship: impedance-void fraction. Develop void fraction models based on the electrical impedance characteristics. By considering slug velocity, void fraction measurement performance is improved. Abstract: This work focuses on the electrical impedance characteristics of slug flow in small channels and its potential on the void fraction estimation. Experiments are carried out with a new contactless impedance detection (CID) sensor in four small channels (1.48mm, 2.02mm, 2.54mm and 2.98mm i.d.). The experimental results show that in small channels there exists scale effect. With the increase of the inner diameter, for the relationships between the imaginary/amplitude part and void fraction, there exist monotonic and regular dispersions. The slug velocity is the root of the regular dispersion and has significant influence on the relationship between the imaginary/amplitude part and void fraction. With the investigated impedance characteristics, void fraction estimation models are developed. The void fraction estimation experimental results indicate that using the imaginary part and the amplitude are effective approaches to realize void fraction estimation in small channels and satisfied estimation performance could be expected.